Electoral Violence and Voter Apathy in North-East Nigeria - Abagen, Franc Ter; Yusuf, Danjuma (Kashere Journal of Politics and International Relations, 2023)
North-East Nigeria is one of the regions of the country that has witnessed electoral violence in the form of killing, kidnapping, rigging, manipulation, and ballot snatching and has equally experienced voter apathy, resulting into low voter turnout during General Elections. In the light of this, this paper examines the causes and nature of electoral violence and voter apathy in the region from 1999 to 2019. Using survey design through the instrumentality of questionnaire with a sample size of 400 respondents including the rational choice theory propounded by Downs (1957) that justifies electoral actions on the premise that all decisions taken by voters are moral, self-interest-driven and applied in compliance with the concept of maximizing the utility of action. The paper discovered that, the causes of electoral violence in the region among others are; provocative utterances by politicians, poverty and illiteracy among the populace, ethnic and religious politics. Also, the causes of voter apathy in the region, among others, are the fear of violence, the feeling that votes do not count, and unfulfilled political promises. Therefore, the work recommends that, inflammatory rhetoric, harassment, and intimidation of opponents by politicians during elections should be criminalized. Politicians as key actors in the political space should fulfil their obligations in a manner that will promote voter participation. Political campaigns should be based on the policies and issues that a party or candidate represents rather than biased identity politics or the attacking of individuals.